Production of Gasoline Using Stable Gas Condensate and Zeoforming Process Products as Blending Components; Energy and Fuels; Vol. 33, iss. 5 - Belinskaya N. S. Natalia Sergeevna; Altynov A. A. Andrey Andreevich; Bogdanov I. A. Ilya Aleksandrovich; Popok E. V. Evgeniy Vladimirovich; Kirgina M. V. Mariya Vladimirovna; Simakov D. David (2019, 2019)
Title screen